Joint Raman spectroscopy and HRXRD investigation of cubic gallium nitride layers grown on 3C‐SiC. Issue 4 (5th January 2016) - Rüsing, M.; Wecker, T.; Berth, G.; As, D. J.; Zrenner, A.
Abstract : Abstractauthoren Cubic gallium nitride (GaN) films are analyzed with high‐resolution X‐ray diffraction (HRXRD) and Raman spectroscopy. Several cubic GaN layers were grown on 3C‐SiC (001) substrate by radio‐frequency plasma‐assisted molecular beam epitaxy. The layer thickness of the cubic GaN was varied between 75 and 505 nm. The HRXRD analysis reveals a reduction of the full‐width at half‐maximum (FWHM) of omega scans for growing layer thicknesses, which is caused by a partial compensation of defects. The Raman characterization confirms well‐formed c‐GaN layers. A more detailed examination of the longitudinal optical mode hints at a correlation of the FWHM of the Raman mode with the dislocation density, which shows the possibility to determine dislocation densities by Raman spectroscopy on a micrometer scale, which is not possible by HRXRD. Furthermore, this Raman analysis shows that normalized Raman spectra present an alternative way to determine layer thicknesses of thin GaN films.